Advances in Health and Environment Safety Select Proceedings of HSFEA 2016 - Siddiqui, N. A.; Tauseef, S. M.; Bansal, Kamal; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book comprises selected papers on advances in the field of health and environment safety that were presented at the leading international conference on advances in the field of health, safety, fire, environment, allied sciences and engineering (HSFEA 2016). The book focuses on the latest developments in the field of health and environment safety, and highlights related opportunities and challenges. The book also presents methods that can be used to effectively monitor and measure climate change and global warming.  Further, the contents of this work stress the importance of maintaining safety and healthy work environments that are free of occupational health hazards. This book will be of interest to researchers, professionals, and policy makers alike.
Health -- Occupational health in engineering, process and agricultural industry -- Effect of vehicular pollution, process, engineering, construction and other industrial activities -- Ergonomics and human factors -- Environment -- Vehicular pollution and control -- Statutory requirements -- Global warming -- Climate change -- Safety -- All the aspects of safety in engineering, process and agricultural industry -- Aviation safety.
Keywords: Security systems; Fire prevention; Buildings -- Protection; Chemicals -- Safety measures; Security Science and Technology; Fire Science, Hazard Control, Building Safety; Chemical Safety